1988
DOI: 10.1099/0022-1317-69-8-1921
|View full text |Cite
|
Sign up to set email alerts
|

Dengue 2 Virus Envelope Protein Expressed by a Recombinant Vaccinia Virus Fails to Protect Monkeys against Dengue

Abstract: SUMMARYA cDNA copy of the dengue (DEN) 2 virus genome region encoding the virion capsid, membrane and envelope structural proteins has been inserted into vaccinia virus (VV) DNA under the control of its 11K late promoter. The DEN-2 envelope protein was expressed and processed in cells infected with the VV recombinant (VV/D2S). No DEN-2 virus antibody response was detected in mice, hamsters or monkeys vaccinated with VV/D2S. Furthermore, a viraemia was observed in recombinant-vaccinated monkeys after challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In recombinant-infected tissue culture cells the inserted cDNAs are expressed and translated into DEN or YF prM and E proteins which are correctly cleaved and modified. Similar results have also been obtained for DEN 4 [3,40] and DEN 2 Jamaica strain [8] suggesting that cleavages to produce flavivirus structural proteins can occur in the absence of the nonstructural proteins. When it becomes possible to construct and study the effects of site-directed mutations on flavivirus structural protein function in the context of virus replication and assembly, such recombinants may allow packaging of mutants with lethal defects in these proteins.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In recombinant-infected tissue culture cells the inserted cDNAs are expressed and translated into DEN or YF prM and E proteins which are correctly cleaved and modified. Similar results have also been obtained for DEN 4 [3,40] and DEN 2 Jamaica strain [8] suggesting that cleavages to produce flavivirus structural proteins can occur in the absence of the nonstructural proteins. When it becomes possible to construct and study the effects of site-directed mutations on flavivirus structural protein function in the context of virus replication and assembly, such recombinants may allow packaging of mutants with lethal defects in these proteins.…”
Section: Discussionsupporting
confidence: 86%
“…Subsequent experiments using weanling mice showed that constructs expressing the DEN 4 structural proteins with or without NS 1 (see below) could protect against fatal DEN 4-induced encephalitis although neutralizing antibody titers were low or not detectable [3]. In studies with a vaccinia recombinant expressing the structural proteins of the Jamaica strain of DEN 2 under the control of the 11 kDa vaccinia late promoter (as opposed to the constitutive 7.5 kDa early/late promoter used in our studies), neither mice, hamsters nor monkeys produced detectable DEN 2 neutralizing antibodies [8]. Furthermore, viremia was still observed in monkeys challenged with DEN 2.…”
Section: Discussionmentioning
confidence: 98%
“…The Autographacalifornicanuclearpolyhedrosisvirus (AcNPV) D2 EA 102 gene was recombined into the AcRp231acZ genome as described previously [4] Several strategies have been explored to produce this antigen in a form that conserves its protective efficacy as evaluated in animal models. DEN E-glycoproteins, produced either in vaccinia or in baculovirus vectors show variations in processing, antigenicity and immunogenic properties [3,4,5,6,11,19,20,26,27]. It is unclear whether the low immunogenicity of some of these E-protein constructs is related to the virus vector, to the DEN serotype or to the nature of the construct.…”
mentioning
confidence: 99%
“…Baculovirus-expressed DEN-1 EA82 protein was intraceltular and was not secreted into the extracellular m e d i u m [20]. The discrepancy in retention between D E N E-proteins is not well [6] or infected with 105 PFU of live DEN-2 Jam virus were used for positive controls. Immunized mice were bled two weeks after the last injection b The yield of recombinant proteins in cell lysate or in extracellular medium was estimated by comparison with bovine albumin standard in Coomassie-stained SDS-PAGE c Pooled sera were obtained by combining equal aliquots from three mice in each experimental group d Sera were analyzed as 1/100 dilutions.…”
mentioning
confidence: 99%
“…There are three non-human primate models that are currently used in dengue studies: Aotus nancymae, Rhesus macaque, and Cynomologous macaque 47,48,49 . Non-human primates develop an asymptomatic dengue virus infection, but have 2 to 5 days of detectable viremia as determined by cell culture isolation 47 .…”
Section: Animal Models For Denguementioning
confidence: 99%